Continuous non‐destructive monitoring of Cyperus rotundus development using a minirhizotron. (1st April 2013) - Shilo, T; Rubin, B; Ephrath, J E; Eizenberg, H; Swanton, Clarence
Summary A new method for non‐destructive monitoring of the subsurface development of Cyperus rotundus (purple nutsedge) is described. A minirhizotron (MR) system was adopted for use to observe vegetative growth of the weed in a net‐house and under field conditions. In particular, the key stages of tuber production and sprouting were monitored and quantified. The MR system allowed non‐destructive repeated measurements of the key stages in C. rotundus subsurface development, serving as a both quantitative and qualitative tool in the study of C. rotundus. A comparison between the MR method and a destructive method revealed that the former reduces experimental variance, thus providing a more accurate prediction of the sprouting process. The techniques presented in the current study offer advanced methodologies for continuous monitoring of C. rotundus development under the soil surface. The novelty of this method lies in its simplicity and efficiency, allowing continuous observation of specific organs of this noxious weed and potentially of other geophytes.